Intermittent theta burst stimulation over the posterior superior temporal sulcus for children with autism spectrum disorder: A 4-week randomized blinded controlled trial followed by another 4-week open-label intervention. (July 2021) - Ni, Hsing-Chang; Chen, Yi-Lung; Chao, Yi-Ping; Wu, Chen-Te; Wu, Yu-Yu; Liang, Sophie Hsin-Yi; Chin, Wei-Chih; Chou, Tai-Li; Gau, Susan Shur-Fen; Huang, Ying-Zu; Lin, Hsiang-Yuan
The posterior superior temporal sulcus is a potential therapeutic target of brain stimulation for autism spectrum disorder. We conducted a 4-week randomized, single-blind parallel sham-controlled trial, followed by additional 4-week open-label intervention to evaluate the feasibility and efficacy regarding intermittent theta burst stimulation over the bilateral posterior superior temporal sulcus in autism spectrum disorder. In total, 78 intellectually able children and adolescents were randomized to the active ( n  = 40) and sham groups ( n  = 38). During the first 4 weeks, the active group received two-session/week intermittent theta burst stimulation, whereas the sham group received the same number of sham stimulation. After unblinding, both groups received eight-session real stimulation over the additional 4 weeks. In total, 91% participants completed the protocol with mild and transitory side-effects. There was no significant group-by-time interaction for active versus sham group on clinical symptoms and social cognitive performances in the first 4 weeks. The within-group analysis revealed 8 weeks (including a 4-week blind trial and a 4-week open-label intervention) of intermittent theta burst stimulation achieved greater efficacy than 4-week interventions. Participants with higher intelligence, better social cognitive performances, alongside less attention-deficit hyperactivity disorder severity at baseline, were more likely to be responders. Our study demonstrated the feasibility of long-term intermittent theta burst stimulation over the posterior superior temporal sulcus in children and adolescents with autism spectrum disorder. However, the findings from the first 4-week blind trial do not support the therapeutic efficacy of intermittent theta burst stimulation over the posterior superior temporal sulcus on the clinical symptoms and cognitive performance of social impairment, given the current stimulation protocol. The exploratory analyses suggest that the therapeutic efficacy might be moderated by several individual characteristics and more intermittent theta burst stimulation sessions. Lay abstract: Intermittent theta burst stimulation is a varied form of repetitive transcranial magnetic non-invasive brain stimulation technique used to treat several neurological and psychiatric disorders. Its feasibility and therapeutic effects on the bilateral posterior superior temporal sulcus in children with autism are unknown. We conducted a single-blind, sham-controlled parallel randomized clinical trial in a hitherto largest sample of intellectually able children with autism ( N  = 78). Participants randomized to the active group received two-session/week intermittent theta burst stimulation for continuous 8 weeks. Those in the sham group received two-session/week sham stimulations in the first 4 weeks and then active intervention for the following 4 weeks after unblinding. First, we found that continuous 8-week intermittent theta burst stimulation on the bilateral posterior superior temporal sulcus in children with autism is safe and tolerable. Second, we found that 8-week intermittent theta burst stimulation produced greater therapeutic efficacy, although we did not find any significant effects of 4-week intermittent theta burst stimulation on core symptoms and social cognitive performances in autism. Further analysis revealed that participants with higher intelligence and better social cognitive performance, alongside less attention-deficit hyperactivity disorder severity at baseline, were more likely to be responders. This study identified that the factors contribute to responders and the results suggest that longer courses of non-invasive brain stimulation may be needed to produce therapeutic benefits in autism, with consideration of heterogeneous responses.